A study on a factor that influence job satisfaction among employees in Majlis Daerah Pontian / Muhammad Saufi Jamil - Jamil, Muhammad Saufi (Faculty of Business and Management, 2014)
This research provides the factors that influence job satisfaction among employees at Majlis Daerah Pontian. The method that researcher used in collection data is primary and secondary data such as questionnaire, text books, journals, interview and others. The main objective in this research is to determine the most factors that influence job satisfaction and also the relationship between each factor with job satisfaction among employees to improve that employee’s performance. Job satisfaction is the important parts in organization where it helps the organization ensure their employees are comfortable and can perform their job as well. Job satisfaction will be dependent variable and the factors of job satisfaction will be the dependent variable. The factors that will tested in this research study on Majlis Daerah Pontian staff which are performance pay, motivation and work environment. The sample for this research study is consisting of 100 employees at Majlis Daerah Pontian. In addition, 84 complete questionnaires had been collected from respondents. To support the study, researcher used primary and secondary data such questionnaires, journals, book texts, interview, and article. In the questionnaire, it was be consist into five parts which are Part A, Part B, Part C, Part D, and Part E. As a conclusion, the researcher fined that performance pay, motivation and work environment have very good strength of the relationship in order to increase employee's job satisfaction at Majlis Daerah Pontian.